2022
DOI: 10.1097/mao.0000000000003765
|View full text |Cite
|
Sign up to set email alerts
|

Distance and Socieoeconomic Status as Barriers to Cochlear Implantation

Abstract: ObjectiveTo assess the distance burden for access to cochlear implant (CI)–related services and to assess whether socioeconomic disadvantage or level of education and occupation influenced uptake of CIs.Study DesignRetrospective case review.SettingA CI services provider operating across multiple centers.PatientsAll patients undergoing CI surgery in a 2-year period between March 2018 and February 2020.Intervention(s)Diagnosis of hearing loss, CI surgery, and subsequent habilitation and mapping.Main Outcome Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Similar findings have been observed in studies conducted worldwide. In Australia, recipients were more likely to live in the least 2 deprived deciles [ 7 ]. Similarly, in the US, adults with private insurance were 13 times more likely to receive cochlear implants compared to those under Medicare cover [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings have been observed in studies conducted worldwide. In Australia, recipients were more likely to live in the least 2 deprived deciles [ 7 ]. Similarly, in the US, adults with private insurance were 13 times more likely to receive cochlear implants compared to those under Medicare cover [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study indicated that adults who had their referral candidacy confirmed with audiometric assessment at an implant centre were more likely to be referred, possibly due to geographical proximity between the patient’s home and the implant centre, but also possibly due to a greater intra-departmental appreciation of cochlear implantation as an option for these patients, and reduced administrative burden in referring these patients to colleagues in the same centre. In Australia, the majority of adult recipients lived near major urban centres [ 7 ]. Among American veterans, rural adults waited longer to obtain both hearing aids and implants, due to longer commutes and lower incomes [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, identifying patient‐specific factors predicting the pursuit of CI surgery is important in determining ways to improve uptake. Previous studies have found longer distances from CI centers, older patient age, racial minorities, and unmarried status negatively affect the likelihood of undergoing implantation 7,16,17 . This study therefore sought to validate and investigate other socioeconomic and patient‐related factors, such as income and employment status, that may impact patients' decision‐making in undergoing CI surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found longer distances from CI centers, older patient age, racial minorities, and unmarried status negatively affect the likelihood of undergoing implantation. 7,16,17 This study therefore sought to validate and investigate other socioeconomic and patient-related factors, such as income and employment status, that may impact patients' decision-making in undergoing CI surgery. In addition, given the higher need for implantation in the elderly population, these factors were reanalyzed in a subset of patients aged 65 years and older to identify changes in the predictor profile.…”
Section: Introductionmentioning
confidence: 99%